EFFECT OF Prosopis juliflora ON AVIFAUNA IN UDAIPUR DISTRICT, RAJASTHAN, INDIA - CHOUDHARY, NARAYAN LAL; CHISHTY, NADIM (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
Prosopis juliflora plant species is an exotic species that is widely spreads in India. Present study (August, 2017 to February, 2020 in Udaipur district, Rajasthan) indicates that abundance of Prosopis juliflora and native floral species were correlated with the bird’s species diversity, richness and abundance. Study divided into four categories on the basis abundance of Prosopis juliflora- very low abundance of Prosopis juliflora (VALPJ), low abundance of Prosopis juliflora (LAPJ), medium abundance of Prosopis juliflora(MAPJ) and high abundance of Prosopis juliflora (HAPJ). Distribution of bird’s species in different area can be directly related to the density of native vegetation and P. juliflora composition. Highest bird diversity and abundance was observed in VLAPJ followed by LAPJ, MAPJ and lowest observed in HAPJ. P. juliflora leads to change in habitat and affect availability of food and nesting sites due to alleo-chemical substance releasing in soils, they inhibit growth of other native plant. Simpson diversity (0.9699) and Shannon diversity (3.872) were maximum observed in VALPJ area and minimum Simpson diversity (0.9556) and Shannon diversity (3.34) observed in HAPJ area. Birds abundance of VALPJ area was (Brillouin = 3.834, Fisher_ alpha= 15.85) maximum and minimum birds abundance was recorded in HAPJ area (Brillouin= 3.227, Fisher_ alpha= 7.541). Highest species richness was observed in VLAPJ (Menhinick= 1.193, Margalef’s= 10.74, Chao-1=95.6) and lowest richness was recorded in HAPJ (Menhinick=1.029, Margalef’s= 5.328, Chao-1=40). Common species like babbler, house sparrow, dove were generally observed in HAPJ area, but environmental sensitive species vultures, kites, eagles and owls were completely absent in high abundance of HAPJ area. Present study shows high abundance of P. juliflora (HAPJ) negatively affects bird’s diversity, abundance and richness. While native vegetations provide better habitat and suitable habitat for birds.